Urgensi Pendidikan Anti Korupsi Pada Generasi Muda Sebagai Agent Of Change Dalam Menumbuhkan Budaya Anti Korupsi Di Indonesia - I Komang Adi Saputra (Ganesha Civic Education Journal, 2022)
Corruption is a big problem that must be faced by Indonesia in moving towards a country that is clean from corruption. Corruption has become a common thing in a country when viewed from corruption cases or crimes that occur in Indonesia which often occur and can be said to be broken and lost and then grow and develop and change without end. The role of the community, especially the younger generation in a country or government, where the key is the attitude and mentality of the community, in this case the younger generation as pioneers to fight corruption practices in the course of a government in a country, is the determinant of steps in managing government that is free from corruption. corruption. Then by cultivating and forming an anti-corruption character and mentality among the younger generation who will be able to emphasize anti-corruption values ​​which can become a prevention of criminal acts of corruption in Indonesia. Furthermore, the younger generation has the potential and role as an agent of change in the progress of a nation. Through anti-corruption education, it can later foster an anti-corruption culture and be able to increase legal awareness of the younger generation. It is also very important to instill legal values ​​in the younger generation.